Faktor-Faktor Yang Mempengaruhi Kepatuhan Pajak Di Kabupaten Sleman - Siti Silatur Rahmi; Myra Andriana; Rahmi, Siti (Universitas Sains dan Teknologi Komputer, 2025)
Since tax revenues are declining annually, it is evident that Indonesian taxpayer compliance is still at a low level. The declining number of taxpayers in KPP Pratama Sleman Regency each year is another indicator of taxpayer compliance and the negative attitude of private taxpayers. The goal of this study is to determine the relative importance of tax penalties, taxpayer knowledge, taxpayer awareness, and taxpayer attitudes. Quantitative approaches are used in this study. The sample in this study consisted of a few KPP Sleman personnel, while the population consisted of 50 respondents, who were KPP Sleman taxpayer consumers. Random sampling was the sampling method employed in this study. Multiple regression is the data analysis method employed, and the analysis's findings indicate that Taxpayer Knowledge of Taxpayer Compliance is attained at t = 9.338 > -4.911ttable with a sig level of 0.00 < sig.α (0.05), meaning that Ha is accepted and H0 is rejected. As a result, H1—the research hypothesis that